Prognosis of different types of acute infection in the first episode of childhood acute leukemia - Li, Shasha; Li, Shanshan; Chen, Yi; Jia, Shuyuan; Luan, Kexin; Cui, Feng (Frontiers in Pediatrics, 2025)
ObjectiveThe aim of the present study was to determine the prognosis of different types of acute infection in pediatric leukemia patients.MethodsA retrospective study was carried out on pediatric leukemia patients with acute infections admitted to the Second Affiliated Hospital of Harbin Medical University between 1 September 2004 and 31 August 2022. Clinical characteristics, diagnostic findings, and prognostic outcomes were extracted from the eligible cases and analyzed.ResultsThere were 36 cases of acute myeloid leukemia (AML) and 72 cases of acute lymphoblastic leukemia (ALL) that met the inclusion criteria. There were significant differences in the incidence of pneumonia (47.2% vs. 27.8%, p = 0.045) and sepsis (19.4% vs. 2.8%, p = 0.006) between the AML and ALL groups. There were 10 cases with a poor prognosis and 26 cases with a favorable prognosis in the AML group. There were no significant differences between the poor prognosis and the favorable prognosis groups except for age (14.2 ± 1.2 years vs. 9.6 ± 4.3 years, p = 0.003). There were 14 cases with a poor prognosis and 58 cases with a favorable prognosis in the ALL group. There were no significant differences between the poor prognosis and favorable prognosis groups except for age (13.4 ± 2.7 years vs. 9.2 ± 4.7 years, p = 0.002).ConclusionsThere were significantly more incidence of pneumonia and sepsis in children with AML. Younger AML and ALL children with acute infections have more favorable prognoses than older children.